Ice Nucleation Measurement and Parameterizations and the Broad Impact of Associated Ocean and Atmospheric Interactions Within the Global Climate - Kristen Tucker (2018)
Current climate models attempt to represent the frequency and characteristics of mixed-phase and ice clouds in the atmosphere. Ice crystals have the ability to scatter incoming solar radiation, which may have a net cooling effect on the Earth’s energy budget. Ice forms in the atmospheric by either homogenous freezing at temperatures colder than -36°C, or by heterogeneous freezing, which requires an ice nucleating particle (INP) to initiate freezing at temperatures warmer than -36°C. The stochastic nature of ice formation requires more rigorous development and testing of model parameterizations that aim to predict ice formation. In this study, we have measured the immersion freezing temperatures of sea surface microlayer (SML) samples collected in the North Atlantic Ocean and used our results to examine the accuracy of a global ice nucleation parameterization to predict marine INP concentrations. SML samples from the fourth NASA North Atlantic Aerosol and Marine Ecosystem Study (NAAMES4) field campaign were evaluated for freezing temperature on a custom built ice microscope. Primary marine aerosols generated by the SML have been found to freeze from -28.041°C to -21.341°C showing they are moderately effective INP. DeMott et al. 2010 developed a global parameterization to predict the concentration of INP that is dependent on both the temperature and size of aerosol particles. To apply the parameterization, Scanning Electrical Mobility Sizer (SEMS) size distribution measurements collected concurrently with the SML samples during NAAMES4 were used to select aerosol particles larger than 0.5m to input into the parameterization. Results of the comparison between observed and predicted number concentration of INP show that the parameterization does not represent the high degree of variability present in the observed concentrations of the marine INP in this study. Further refinement of this global parameterization may improve its ability to accurately predict number concentrations of INP produced in a marine ...